Impact of chemical exposure on the fish Pomatoschistus microps Kroyer (1838) in estuaries of the Portuguese Northwest coast - Monteiro, M.
Juveniles of the estuarine fish Pomatoschistus microps were collected from autumn 2001 to summer 2002 in five stations along the Portuguese Northwest coast with different types and/or levels of environmental contamination: two reference sites with low levels of contamination (R1 and R2) and three differently impacted areas with higher levels of contamination. UI is located in an estuary under the influence of urban and industrial effluents, AA in a channel that receives intensive agriculture run-off and IE in a highly impacted industrial area. The activity of the enzymes acetylcholinesterase (AChE), lactate dehydrogenase (LDH), 7-ethoxyresorufin O-deethylase (EROD) and glutathione S-transferases (GST) were used as environmental biomarkers on P. microps. A significant seasonality effect on all the enzymatic activities was found, lower levels being registered in winter and spring on AChE, in autumn on LDH, and in winter on GST and EROD. The battery of biomarkers used was capable of discriminating sites with different types and/or levels of contamination, R1 and UI being the highest discriminated (91.7% and 66.7%, respectively). At R1 significantly lower levels of AChE and LDH were found, and EROD was significantly inducted at UI. Furthermore, IE presented higher levels of GST, and R2 and AA an inhibition of AChE in winter and spring. The results indicated that the battery of biomarkers used in this study seems to be a useful tool to distinguish between different types of environmental contamination in estuarine systems, and that P. microps is a suitable species to be used as bioindicator. (c) 2006 Elsevier Ltd. All rights reserved.